Design, Synthesis, Cytotoxicity Profiling, Molecular Docking and ADMET Studies of Novel Functionalized Coumarin-pyrazole-thiazole Hybrids: Cyclization of Chromonyl Thiazolyl Pyrazolyl Thiosemicarbazone with α-Halocarbonyl Reagents - Ali, Tarik E.; Alsolimani, Ayat K.; Assiri, Mohammed A.; Shati, Ali A.; Alfaifi, Mohammad Y.; Elbehairi, Serag E. I. (Current Organic Chemistry, 2025)
A simple synthetic method was performed to design a novel series of polycyclic systems consisting of a coumarin-pyrazole-thiazole skeleton linked with a completed thiazole ring via hydrazone linkage. The methodology depended on the cyclization of the active precursor 2-[(3-(2-oxo-2H-chromen-3-yl)-1-(4-phenylthiazol-2-yl)-1H-pyrazol-4-yl)methy-lene]hydrazine-1-carbothioamide (2) by its reaction with a series of α-halocarbonyl reagents under Hantzsch reaction conditions. The spectral and analytical data confirmed the structures of all the synthesized compounds. The target compounds were screened for their in vitro anticancer activity. The cytotoxic effects of obtained compound were screened against cancer cell lines (MCF-7, HepG2, and HCT116) using the standard SRB method. Furthermore, products 4, 5, and 7b were the most active against all cancer cell lines, compared with Doxorubicin. These bioactive products effectively suppress the growth of cancer cells by activating the cell death program through late apoptosis. In addition, products 4 and 5 arrested the cell cycle at the S and G2 phases, while product 7b has the ability to arrest the cell cycle at the G2 phase against all three cancer cells. The molecular docking of the products 4, 5, and 7b showed good binding affinities with Cyclin-dependent kinase 8 (CDK-8), while the ADMET prediction supported that these bioactive products can be promising anticancer agents.
Keywords: cytotoxic